Analisis Perbandingan Efektivitas Pendinginan Radiator Menggunakan Variasi Nanofluida Al2O3 dan Air pada Sistem Pendingin Mesin Mobil - Taufiq Hidayatno; muhamad safii; althesaanadrova (Jurnal Ilmiah Teknik Mesin, Elektro dan Komputer, 2026)
The engine cooling system plays a crucial role in maintaining the engine's working temperature within an optimal range. This study aims to analyze and compare the cooling effectiveness of a radiator using Al2O3 nanofluid at 0.3% volume concentration against water as a conventional coolant. Tests were conducted on an automotive engine at engine speed variations of 1000, 1500, 2000, 2500, and 3000 RPM. Measured parameters included radiator inlet and outlet temperatures, mass flow rate, and heat transfer efficiency. Results show that 0.3% Al2O3 nanofluid achieved an average cooling effectiveness of 19.16%, compared to 15.53% for water. The 4.6% increase in thermal conductivity of the nanofluid contributed significantly to improved heat transfer in the radiator. This study concludes that 0.3% Al2O3 nanofluid is an effective alternative for improving automotive engine cooling system performance.